Muhāwālātu Tākwini Māhārāti ān-Nāhwiyyāh Bii Tāthbiqi Tā’limi ān-Nāhwi āl-Qāim ‘Alā Mādzhābi āl-Kufāh Fii Mā’hādi ‘Adnān āl-Chārish Bojonegoro - Nurul Musyafaah; Mas Tajuddin Ahmad; Fatya Nia Rahmawati; Khabib Syaikhu Rohman; Muhammad Afthon Ulin Nuha (Mantiqu Tayr: Journal of Arabic Language, 2024)
This grammar study aims to provide students with the necessary tools to read Arabic books. Learning grammar starts with easy-to-understand material. The Grammar book is generally used as primary materials, and the goal is to obtain the appropriate tools for understanding and mastering the Arabic language. Teaching grammar also attempts to overcome many problems, such as students’ boredom or difficulties they face in understanding the material. Although there are differences within the grammar school, Islamic educational institutions tend to focus on presenting grammatical materials according to popular texts. However, the differences in grammar schools can enrich thinking about grammar and Arabic sciences. This research will explore the effects of the Kufic grammar method in improving the grammar skills of beginners at the Adnan Al-Haris Institute. This research will collect data from 82 students of Islamic boarding schools in Adnan Al-Haris Institute, and will consider the impact of grammar teaching on students' grammatical skills. In this discussion, the grammar pattern of Kufa in Adnan Al-Haris Islamic Boarding School will be explained. In this research, the researcher chose the appropriate type of method and approach. This types of research is Library Research, this research consists of introduction, research methodology, results until conclusion, the Participant in this research is santri in Adnan Alcharis Boarding School and this is designed by qualitative research. The research uses the qualitative research method or the desk research method. In conclusion, teaching grammar according to the Kufa doctrine can improve grammatical skill. Future research is hoped to develop grammatical skills using the other type of Madzhab in Nahwu.